SIA „Lana” saimnieciskās darbības analīze un attīstības tendences - Zolotova, Nataļja (Latvijas Universitāte, 2011)
Maģistra darba „SIA LANA saimnieciskās darbības analīze un attīstības tendences” aktualitāti pamata uz uzņēmuma saimnieciskās darbības analīzes un attīstības perspektīvu novērtēšanas nepieciešamību, ka arī uz nepieciešamība noteikt finanšu stabilitates līmeni un atklāt uzņēmuma darbības kļūdas. Darba mērķis – izanalizēt SIA „Lana” saimnieciskās darbības īpatnības un noteikt tās attīstības perspektīvas, kā arī sniegt priekšlikumus sekmīgai uzņēmuma attīstībai. Pētījuma galvenie uzdevumi ir: veikt Latvijas būvniecības nozares analīzi, analizēt uzņēmuma galvenas finanšu rādītājus, sniegt bankrota varbūtības novērtējumu, izpētīt uzņēmuma ietekmējošas faktorus un dot priekšlikumus uzņēmuma darbības uzlabošanai. Maģistra darbs sastāv no trim daļām un ietilpst 82 lappuses. Pirmajā daļā ir apskatīta Latvijas būvniecības nozare un uzņēmuma vieta nozarē. Otrā daļa veltīta SIA „Lana” saimnieciskās darbības analīzei, kurā iekļauj uzņēmēdarbības raksturojums un finanšu analīze. Trešajā daļā autore izveikusi krīzes stāvokļa ietekmējošo faktoru analīzi, ka arī izstrāda uzņēmuma stabilizēšanas pasākumus, kas ir virzīti uz uzņemuma darbības pilnveidošanu un finansiālā stāvokļa uzlabošanu. Svarīgākie informācijas avoti – LR likumdošanas akti, diplomdarba tēmai atbilstoša zinātniskā literatūra, statistikas dati, publikācijas periodikā, interneta resursi kā arī SIA “Lana” gada pārskati un nepublicēti materiāli. Atslēgas vārdi: ekonomiska lejupslde, saimnieciskas darbības analīze, finanšu stabilitāte, maksātspēja.

The actuality of the master’s work “Lana” LLC analysis of economic activity and the trends in it’s development” is based on the necessity to evaluate the company’s economic activity and the perspectives for development, as well as to define the level of the financial stability and to demonstrate the mistakes made in company’s activity. The goal of the work - to make an analysis of the peculiarities of “Lana” LLC economic activity and to define it’s development perspectives, as well as to formulate the suggestions for the company’s further successful functioning. The main tasks of the work are the following: to analyze the construction branch of the Latvian market, to analyze the company’s main financial indexes, to present the evaluation of the bankruptcy risks, to examine “Lana” LLC influencing objectives and to work out the proposals for the amelioration of the company’s activity. The graduation work consists of three parts and contains 82 pages. In the first part the Latvian construction branch has been examined as well as the place of “Lana” LLC in the market has been defined. The second part is devoted to the analysis of economic activity of the company. This analysis includes the characteristic of the company’s activity and the financial evaluation. In the third part the author has analyzed the factors which have influenced the company’s critical financial situation and has worked out stabilization measures. These measures are to fulfil the company’s activity and to improve company’s financial stability. The most important information issues for the master’s work are the following: legislative acts of the Latvian Republic, scientific literature corresponding the theme of given graduation work, statistics and publications in the periodic, internet resources, annual reports and non-published information about “Lana” LLC. The key words: recession, the analysis of economic activity, financial stability , ability to pay.
"Lana" LLC analysis of economic activity and the trends in it's development
Keywords: Ekonomika